TERAPI AKTIVITAS KELOMPOK (TAK) STIMULASI PERSEPSI DALAM MENURUNKAN TINGKAT KECEMASAN PADA LANSIA - Khamida, Khamida; Meilisa, Meilisa (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2016)
Success elderly people are those who are active, does not work, follow elderly integrated health service (HIS), have healthy lifestyle, , cheerful, and able to maintain their health. The purpose of this study was to determine the effect of Activity Group Therapeutic (AGT) Perception Stimulation on Anxiety Levels at Elderly in Damarsi village Buduran Sidoarjo.Study design is Quasi Experiment with pre-post test control group approach, the population were entire elderly with amount 75 person, some of them 34 respondents taken as sample by simple random sampling method. The independent variable is Activity Group Therapeutic (AGT) Perception Stimulation, the dependent variable is anxiety. Study instrument use questionnaire, observation sheet. Statistical test use Wilcoxon test with a significance level α = 0.05.The result of the study before the daily routine of 22 respondents are the control group anxiety level was 59,1%, and after the daily routine there is a level of anxiety was 68,2%. While 12 respondents treatment group before (AGT) there is anxiety level was 100% and after (AGT) are mild anxiety level of 75,0%. Wilcoxon test showed the treatment group ρ = 0,003, ρ < α means no influence Activity Group Therapeutic (AGT) Perception Stimulation of the level of anxiety in the elderly in the village Damarsi Buduran Sidoarjo.Elderly anxiety level can be scaled by one of them Activity Group Therapeutic (AGT) Perception Stimulation. Suggestions for the elderly to play an active role in these activities to lower levels of anxiety.